2021
DOI: 10.18786/2072-0505-2021-49-070
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of an isolated hind legperfusion with a pH-increased solution in thePliss’ lymphosarcoma graft rat model

Abstract: Background: The technique of regional isolated perfusion makes it possible to increase local levels of an anti-tumor agent, to perform the treatment procedure under hypothermia or hyperthermia, to reduce or even eliminate any systemic effect of a cytostatic on the patient. In this context, the use of isolated perfusion to modify the pH milieu of the tumor seems to be a promising strategy that could potentially ensure the anti-tumor effect. Aim: To evaluate the efficacy of a rat limb perfusion with 4% NaH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In another study, perfusion was performed with a 4% sodium bicarbonate solution of rat limbs with a Pliss lymphosarcoma graft. The median survival in the sodium bicarbonate group was 17 days, while in the nonperfused group and in the isotonic saline group it was 13 days ( 17 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, perfusion was performed with a 4% sodium bicarbonate solution of rat limbs with a Pliss lymphosarcoma graft. The median survival in the sodium bicarbonate group was 17 days, while in the nonperfused group and in the isotonic saline group it was 13 days ( 17 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…The acidity of the TME could be used for the drug delivery of cytotoxic agents and/or carriers that are more active and/or change physicochemical properties under such conditions ( 11 13 ). It is very attractive to increase the pHe by a combination of an alkaline diet and bicarbonate therapy ( 14 16 ) or by direct local isolated perfusion of the tumor with bicarbonate solutions ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we examined the effects of a single perfusion using a 4% sodium bicarbonate solution on rat limbs with a Pliss lymphosarcoma graft. We found that the median survival period for the sodium bicarbonate group was 17 days, which was longer than both the nonperfused group and the isotonic saline group, which had median survival periods of 13 days ( 13 ). The clinical study ChiCTR-IOR-14005319 evaluated and compared the efficacies of conventional transarterial chemoembolization (TACE) and targeting intratumoral lactic acidosis TACE (TILA-TACE) with the local administration of a 5% sodium bicarbonate solution in patients diagnosed with large-focal hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 90%